Implementasi Perangkat Pembelajaran Berbasis Masalah Pada Penataan Sanggul Up Style Untuk Meningkatkan Hasil Belajar Mahasiswa Di Universitas PGRI Adi Buana Surabaya - Vony Fatmawati Hipij (LPPM Universitas PGRI Adi Buana Surabaya, 2016)
Developments in science and technology requires qualified human resources, able to develop and master the science technology through learning activities that can improve student learning outcomes in the cognitive, affective and psychomotor domains which automatically takes the role of tools and learning models. One type of learning model that can meet the needs for human resources capable of developing science and technology is a learning model based on the problem. Research design used in this research is the development of research design pattern and post-test one group pretest design. In this study the development of statistical hypothesis test results obtained using a sign test grades count ≥ h h table. Mastery learning outcomes of students in each school with a learning model based on the problem gained mastery of 79.98% at class experimental and 76.69% at class control in adibuana university of Surabaya with KKM value by 70%. Completeness of the results obtained it can be concluded from the results of the implementation of the development of a learning device based on the competency issue bun up styles to improve student learning outcomes well. Keywords: Learning tool, Problem based instruction, Mastery learning